DETERMINANTS OF HEAVILY DAMAGED FIXED ASSETS MANAGEMENT SUCCESSFUL MODERATED BY LEADER COMMITMENT - Lia Yulianti; Wuryan Andayani; Abdul Ghofar (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The objective of this research is to examine the effect of human resource (HR) competence, supervision and control, and regulation on successful damaged fixed assets management moderated by leader commitment in central government. The research was conducted at the Ministry of Public Works and Housing (PUPR) with 139 respondents whose selection was carried out with certain criteria or judgmental sampling method. The sample consists of employees who are accustomed to processing damaged fixed assets management so that they are expected to have a good understanding of State-Owned Assets (BMN) management. The data analysis method uses SEM-PLS with the help of the SmartPLS 3.0 program. The results showed that HR competence, supervision and control, and regulation positively affect the successful damaged fixed assets management. Furthermore, leader commitment as a moderating variable cannot strengthen the relationship between HR competence on the successful damaged fixed assets management, weaken the relationship between supervision and control on the successful damaged fixed assets management, but can strengthen the relationship between regulation on the successful damaged fixed assets management.